Identifying and comparing meteorological and geographical influences on high resolution climate signals in the oxygen isotope values of different environmental archives - Thompson, EM (2018)
This thesis explores how δ18O values in horse hair relate to local meteorological observations; how Greenland ice core records relate to European terrestrial climate records; and how atmospheric changes are reflected in terrestrial and biological records. Bringing together analysis of increasingly complex palaeoenvironmental proxies, δ18O measurements within atmospheric, terrestrial and biological systems are critically assessed across geographical transitions, ultimately leading to greater understanding of the utilisation of oxygen isotope data for seasonal climate analysis. Horse hair sampling and δ18O analysis were conducted on horse hair from: the Icelandic Food and Veterinary Authority (MAST) in Selfoss, Iceland; the Thordale Stud in the Shetland Islands, United Kingdom; the Exmoor Pony Centre (EPC) in Somerset, UK; and the Pigeon House Equestrian centre in Oxfordshire, UK. The North Greenland Ice Core (NGRIP2) was sampled and analysed for δ18O, and compared to a master tree ring dataset of compiled δ18O values in the UK. The results confirm that rainfall quantity and continental effects dominate both the horse hair and ice core δ18O records. The growth rates of the hair were seen to decrease with an increase in latitude; and comparison between horse hair δ18O and meteorological variables clearly indicates a rainfall influence. Comparison between the ice core δ18O and historical coastal temperature reconstruction shows a similar gradient to what is seen in modern temperature records. The comparison between tree ring isotopes can be interpreted as showing a similar amplitude to the historic temperatures, but with a slight dampening in regards to lower peaks values. Comparison of the tree ring and ice core values indicated a significant negative correlation, with smaller amplitude changes within the tree ring δ18O results. Wavelet analysis suggested a common influence from teleconnections at several timescales in both the tree ring and ice core datasets, including the El Niño Southern Oscillation and the North Atlantic Oscillation. This study demonstrates that geographical and meteorological influences are similarly reflected within palaeoenvironmental proxies of increasing complexities. It also identifies periods of common influence from climate drivers and provides detail of the greatest effects on isotopic variation in the UK, Iceland and Greenland.